Gulliver's Travels - Swift, Jonathan; Chestney, Lillian; Swift, Jonathan, 1667-1745. (Sydney : Ayers & James, 1952)
The story of Gullliver's adventures among the six-inch high Lilliputions.
Published by Ayers & James, Sydney, by arrangement with Gilberton Company, New York.
Keywords: Gulliver, Lemuel (Fictitious character) -- Comic books, strips, etc